The effectivity of pimaricin and pH adjustment in retarding the spoilage of Ladu orange juice - Ramos, Juanita G.; De Leon, Sonia Y. (1968.)
The efficacy of pimaricin as a preservative in frozen and pre-srozen ladu orange juice was evaluated. The juice samples were treated to contain 0, 10 and 20 ppm pimaricin and were adjusted to and maintained at pH 3.00, at its natural pH 3.60 and pH 4.50. Fungicidal activity ws exhibited by 20 ppm from the start, the rate being fastest at pH 3.00 and slowest at pH 4.50. Ten ppm pimaricin showed fungicidal activity only after 1 week. The efficacy of pimaricin was enhanced by a lower pH. Refractometric readings and percent surviving yeasts data correlated very well with the growth data. They showed that 10 and 20 ppm pimaricin may retard yeast and mold activity, the efficiency increasing with decreasing pH of the juice samples. Results of the presumptive identification of the surviving organisms showed the presence of yeasts, mold of the genus Cestrichum and bacteria of the genera Leuconostoc, Staphylococcus, Zymemonas and Escherichia in ladu orange juice.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Orange juice; Food preservatives